Maternal Contribution in Revealing The Effects of Methoxyacetic Acid (MAA) Administered Before Implantation on The Embryonic Development of Swiss Webster Mice (Mus musculus) - Kaiin, Ekayanti M; Sumarsono, Sony H.; Surjono, Tien W.; Sudarwati, Sri (Annales Bogorienses, 2004)
Maternal contribution to and direct action of methoxyacetic acid (MAA) on the embryonic development bad been examined by conducting embryo transfer. To reveal the maternal contribution, compacted morulae and early blastocysts, which were collected from untreated Swiss Webster donor mice on day 3 of gestation, were transferred to day 2 pseudopregnant recipients, after having been treated with 2.0 mmo/lkg body weight (b.w.) MAA by gavage on day 1 of pseudopregnancy. Direct effect of MAA on the embryonic development were observed by transferring compacted morulae and early blastocysts, similarly recovered from day 3 pregnant donor mice, after MAA treatment on day 2 of gestation with the same method and dosing, to untreated day 2 pseudopregnant recipients. Control donor mice and recipient were given distilled water only as the MAA solvent. Observations on fetuses resulting from embryo transfer wert: carried out on day 16 of gestation . Administration of MAA to the donors tended to decrease the unplantatlon rate and the survival rate of the implanted embryos. When MAA was given to the recipients the implantation rate and survival rate of embryos transferred decreased significantly (p<0.05) but the survival rate of implanted embryos were significantly higher (p<0.05) Lf compared to those of MAA treated donors. The intrauterine death tended to inc rease either in the treated donors or recipients. There was no effect of MAA on the fetal body weight and in producing fetal malformations. It is concluded that at the beginning of implantation, maternal contribution in revealing the effects of MAA on the embryonic development of Swiss Webster mice is predominant, whereas after implantation took place, the quality of the embryos become more important for their survival.